2018
DOI: 10.1002/jwmg.21419
|View full text |Cite
|
Sign up to set email alerts
|

Wolf‐livestock conflict and the effects of wolf management

Abstract: Wolf (Canis lupus) depredations of livestock are a ubiquitous source of conflict in every country where wolves and livestock overlap. We studied the spatial and temporal variation of wolf depredations of livestock in Montana during 2005-2015, including evaluations of targeted control efforts and public harvest as potential means to reduce depredations. During this time we collected spatial data for all confirmed wolflivestock depredations, tallied the annual number of depredation events within hunting district… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Successful management of the conflict between expanding wolf populations and livestock husbandry requires insights into patterns of depredation on livestock and related factors (Behdarvand et al, 2014; Breck & Meier, 2004). Several factors have been proposed to explain the probability and numbers of wolf attacks, including the density of wolf populations, pack sizes, availability of natural prey, landscape structure, livestock availability, husbandry practices, and protective measures (Bradley et al, 2015; DeCesare et al, 2018; Janeiro‐Otero et al, 2020; Kaartinen et al, 2009; Kaczensky, 1999; Meriggi & Lovari, 1996; Odden et al, 1999). Given the variety of factors influencing livestock depredation by wolves, it is difficult to predict spatial and temporal patterns in wolf attacks, especially in areas where wolves are recolonizing after a long absence (Dalerum et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Successful management of the conflict between expanding wolf populations and livestock husbandry requires insights into patterns of depredation on livestock and related factors (Behdarvand et al, 2014; Breck & Meier, 2004). Several factors have been proposed to explain the probability and numbers of wolf attacks, including the density of wolf populations, pack sizes, availability of natural prey, landscape structure, livestock availability, husbandry practices, and protective measures (Bradley et al, 2015; DeCesare et al, 2018; Janeiro‐Otero et al, 2020; Kaartinen et al, 2009; Kaczensky, 1999; Meriggi & Lovari, 1996; Odden et al, 1999). Given the variety of factors influencing livestock depredation by wolves, it is difficult to predict spatial and temporal patterns in wolf attacks, especially in areas where wolves are recolonizing after a long absence (Dalerum et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Such efforts lean heavily on deterrents aimed at preventing depredation, frequently positioned as "nonlethal alternatives" to the lethal control of "problem individuals." While these tools and techniques are often described as "straightforward" (Western Wildlife Outreach, 2014), questions remain around their effectiveness and associated costs (on the efficacy and ethics of lethal vs. nonlethal wildlife management, see Miller et al, 2016;Eklund et al, 2017;DeCesare et al, 2018;Lennox et al, 2018;Moreira-Arce et al, 2018;van Eeden et al, 2018;Treves et al, 2019;Gamborg et al, 2020;Boronyak et al, 2021).…”
Section: What Does Coexistence Mean?mentioning
confidence: 99%
“…Nonetheless, in the USA, attack recurrence decreases for farms equipped with traps as compared with non-equipped farms, but with no effect at the state level (Harper et al 2008). DeCesare et al (2018) showed that increasing levels of targeted lethal removal of wolves following depredation reduced the probability of their recurrence at the level of a hunting district. Although Wielgus and Peebles (2014) found a counter-intuitive result with lethal control leading to an increase in livestock depredation, their analysis has been contested by both Poudyal et al (2016) and Kompaniyets and Evans (2017) who found statistically negative effects of lethal removal on subsequent depredation.…”
Section: Is There a Solution Pathway?mentioning
confidence: 99%